Study on High-Strength Ring Chain Dynamic Characteristics under Different Launch Parameters - Zhang, Q.; Liu, J.M.; Liu, Y.F.; Li, L.Y. (Проблемы прочности, 2018)
The aim of this study is to investigate the mechanical characteristics of the high-strength ring chain under various launch parameters and the energy consumption caused by this. Particularly, the contact dynamics simulation was implemented in ABAQUS to study the launch characteristics impacted by different chain speeds different transportation loads, and the results were proved by experiments. The results show that stable stresses under different launch speeds are diverse, and the launch speed which makes the performance best is 5.6 m/min; stable stresses under different loads are diverse, and in the overload-launch process, the normal force of the chain increases multi-fold so that the chain will be great damaged; The energy consumption caused by the friction among high-strength ring chains under no-load operation occupies 23.8% of the resistance consumption. With the rise in loads, the total resistance consumption grow linearly. As a consequence, the research has great significance for the research of ring chain launch characteristics, the forecast of the chain's operating life and the efficiency improvement of electromotors.